Altered Ca2+ Kinetics Associated with alpha-Actinin-3 Deficiency May Explain Positive Selection for ACTN3 Null Allele in Human Evolution - Head, Stewart I.; Chan, Stephen; Houweling, Peter J.; Quinlan, Kate G. R.; Murphy, Robyn; Wagner, Sören; Friedrich, Oliver; North, Kathryn N. (PLoS Genetics, 2015)
Over 1.5 billion people lack the skeletal muscle fast-twitch fibre protein alpha-actinin-3 due to homozygosity for a common null polymorphism (R577X) in the ACTN3 gene. alpha-Actinin-3 deficiency is detrimental to sprint performance in elite athletes and beneficial to endurance activities. In the human genome, it is very difficult to find single-gene loss-of-function variants that bear signatures of positive selection, yet intriguingly, the ACTN3 null variant has undergone strong positive selection during recent evolution, appearing to provide a survival advantage where food resources are scarce and climate is cold. We have previously demonstrated that alpha-actinin-3 deficiency in the Actn3 KO mouse results in a shift in fast-twitch fibres towards oxidative metabolism, which would be more "energy efficient" in famine, and beneficial to endurance performance. Prolonged exposure to cold can also induce changes in skeletal muscle similar to those observed with endurance training, and changes in Ca2+ handling by the sarcoplasmic reticulum (SR) are a key factor underlying these adaptations. On this basis, we explored the effects of alpha-actinin-3 deficiency on Ca2+ kinetics in single flexor digitorum brevis muscle fibres from Actn3 KO mice, using the Ca2+-sensitive dye fura-2. Compared to wild-type, fibres of Actn3 KO mice showed: (i) an increased rate of decay of the twitch transient; (ii) a fourfold increase in the rate of SR Ca2+ leak; (iii) a threefold increase in the rate of SR Ca2+ pumping; and (iv) enhanced maintenance of tetanic Ca2+ during fatigue. The SR Ca2+ pump, SERCA1, and the Ca2+-binding proteins, calsequestrin and sarcalumenin, showed markedly increased expression inmuscles of KO mice. Together, these changes in Ca2+ handling in the absence of a-actinin-3 are consistent with cold acclimatisation and thermogenesis, and offer an additional explanation for the positive selection of the ACTN3 577X null allele in populations living in cold environments during recent evolutio